RIME and Reason - Gururangan, Kapil; Lin, Steven (Journal of Student-Run Clinics, 2018)
Student-run free clinics (SRFCs) are unique clinical settings that combine service to underserved populations and medical student education. SRFCs empower students to take charge of real patients’ care prior to entering clerkship rotations. This real-world education, by fostering an early experience of clinical responsibility, helps students prepare for the role transitions described by the RIME (Reporter-Interpreter-Manager-Educator) framework that defines the training and development of physicians – from reporters and interpreters of clinical data, to patient care managers, to educators of the next generation. We present a narrative of one medical student’s formative experiences at SRFCs during his preclinical and early clinical years to highlight their value in preparing students for their future careers.